Spontaneous Self-Assembly of Single-Chain Amphiphilic Polymeric Nanoparticles in Water - Huang, Shan-You (Nanomaterials (Basel), 2020)
Single-chain polymeric nanoparticles (SCPNs) have great potential as functional nanocarriers for drug delivery and bioimaging, but synthetic challenges in terms of final yield and purification procedures limit their use. A new concept to modify and improve the synthetic procedures used to generate water-soluble SCPNs through amphiphilic interactions has been successfully exploited. We developed a new ultrahigh molecular weight amphiphilic polymer containing a hydrophobic poly(epichlorohydrin) backbone and hydrophilic poly(ethylene glycol) side chains. The polymer spontaneously self-assembles into SCPNs in aqueous solution and does not require subsequent purification. The resulting SCPNs possess a number of distinct physical properties, including a uniform hydrodynamic nanoparticle diameter of 10–15 nm, extremely low viscosity and a desirable spherical-like morphology. Concentration-dependent studies demonstrated that stable SCPNs were formed at high concentrations up to 10 mg/mL in aqueous solution, with no significant increase in solution viscosity. Importantly, the SCPNs exhibited high structural stability in media containing serum or phosphate-buffered saline and showed almost no change in hydrodynamic diameter. The combination of these characteristics within a water-soluble SCPN is highly desirable and could potentially be applied in a wide range of biomedical fields. Thus, these findings provide a path towards a new, innovative route for the development of water-soluble SCPNs.